2020
DOI: 10.1093/imrn/rnaa068
|View full text |Cite
|
Sign up to set email alerts
|

Generic IllPosedness for Wave Equation of Power Type on Three-Dimensional Torus

Abstract: In this article, we prove that the equationThis work also indicates that, only properly regularizing the initial data can we smoothly approximate the solutions constructed in [2] and [12].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…When s ≥ 1 2 , local well-posedness of (3.1) in H s (T 3 ) follows from a standard fixed point argument with the (deterministic) Strichartz estimates. Moreover, the equation (3.1) is known to be ill-posed in H s (T 3 ) for s < 1 2 [26,21,90]. In the following, we take initial data (u 0 ,…”
Section: Probabilistic Well-posedness Of Nlw and Nlsmentioning
confidence: 99%
See 3 more Smart Citations
“…When s ≥ 1 2 , local well-posedness of (3.1) in H s (T 3 ) follows from a standard fixed point argument with the (deterministic) Strichartz estimates. Moreover, the equation (3.1) is known to be ill-posed in H s (T 3 ) for s < 1 2 [26,21,90]. In the following, we take initial data (u 0 ,…”
Section: Probabilistic Well-posedness Of Nlw and Nlsmentioning
confidence: 99%
“…(v) Unlike the usual deterministic theory, the approximation property of the random solution u ω constructed in Theorem 3.1 by smooth solutions crucially depends on a method of approximation. On the one hand, Xia [90] showed that the solution map: (u 0 , u 1 ) → u for (3.1) is discontinuous everywhere in H s (T 3 ) when s < 1 2 . This in particular shows that the solution map for (3.1), a priori defined on smooth functions, does not extend continuously to rough functions, including the case of the random initial data (u ω 0 , u ω 1 ) considered in Theorem 3.1.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…Norm inflation based at general initial data has been studied for NLW [50,47] and NLS [38] in negative Sobolev spaces. We establish norm inflation at any u 0 ∈ H s (M), with s < 0, for the BBM equation 1.…”
Section: Justin Forlanomentioning
confidence: 99%